Angle-resolved photoemission of ultrathin Pb films on Si(111)-(6×6)Au: quantum size effect - Kisiel, Marcin; Skrobas, Kazimierz; Jałochowski, Mieczysław (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
The electronic band structure of extremely thin (from 1 to 8 monoatomic layer (ML) thick) epitaxial Pb(111) films grown at low temperatures in ultrahigh vacuum (UHV) condition on Si(111)-(6×6)Au substrate is studied with angle-resolved photoelectron spectroscopy (ARPES). The morphology of the Pb film is determined with scanning tunneling microscopy (STM). Normal-emission photoelectron spectra recorded at the sample temperature of 130 K reveal quantum well states (QWS) characteristic of quantization perpendicular to the film surface. The energies of these states as a function of the number of the Pb(111) monoatomic layers are determined and compared with calculated in terms of the Bohr–Sommerfeld phase accumulation model.
Optica Applicata, Vol. 35, 2005, nr 3, s. 443-448
Keywords: optyka; quantum wells; Pb; angle-resolved photoelectron spectroscopy